An evaluation of cadaver- and manikin-based surgical airway simulation training for emergency medicine resident doctors - Emel Altintas; Ceren Gunenc Beser; Tugce Taskindere Abbasoglu (Scientific Reports)
Abstract In rare cases in which endotracheal intubation is impossible, surgical airway interventions may be needed. Therefore, we evaluated and compared manikin- and cadaver-based surgical airway simulation training programmes for emergency medicine resident doctors (EMRDs) on the basis of the analyse, design, develop, implement, and evaluate (ADDIE) model. The thirty-one EMRDs who were included in the study first participated in a pretest. The participants were divided into two groups, i.e., a manikin-based surgical airway simulation training group (group M) and a cadaver-based surgical airway simulation training group (group C); the researchers ensured the absence of any differences between the groups in terms of participants’ pretest scores and whether they had less or more than two years of experience. Sixteen EMRDs practiced the skill in question on a whole-body cadaver, and 15 EMRDs practiced the skill on a 3D-printed cricothyrotomy model. Their performance was evaluated on the basis of the first two levels of the Kirkpatrick model. The reactions of these EMRDs were evaluated via a surgical airway simulation training programme satisfaction survey that was scored on 5-point Likert-type scale (1st level – reaction), and their levels of learning were evaluated via the cricothyrotomy skill assessment guide at baseline and one month later (2nd level – learning). Five participants in each group dropped out of the study during the skill assessment process. The average score on the satisfaction survey reported by participants in group C was 4.85 ± 0.16, and the average score reported by participants in group M was 4.82 ± 0.20. No statistically significant differences were observed between the average scores of participants in the two groups (p = .623). More than half of the EMRDs in both groups performed the cricothyrotomy procedure successfully in their first set of attempts (group C success rate: 56.3%; group M success rate: 73.3%). However, the EMRDs in group M were significantly more successful than were those in group C (p < .01). One month later, the success rates on the procedure exhibited by the EMRDs in both groups were 100%. The EMRDs were satisfied with both the cadaver- and manikin-based surgical airway simulation training. Most of the EMRDs in both groups performed the cricothyrotomy procedure successfully in their first set of attempts, and their success rates increased when they performed the procedure again one month later.